Effect of silencing CITED1 gene to regulate PI3K/AKT pathway on the biological function of PTC cells and its mechanism: Effect of CITED1 on papillary thyroid carcinoma - Chen, Wanzhi; Yu, Jichun; Xie, Rong; Zhang, Shuyong; Zhou, Tao; Xiong, Chenfeng; Huang, Da; Zhong, Meijun (Cellular and Molecular Biology, 2023)
This study aims to investigate the effect of silencing the CITED1 gene to regulate the PI3K/AKT pathway on the biological function of papillary thyroid carcinoma (PTC) cells and its mechanism of action. Human PTC cells SW1736 were divided into 4 groups: control group, siCITED1 group, LY294002 group and siCITED1+LY294002 group. CITED1 was silenced by transfection with siCITED1 plasmid. The PI3K/AKT pathway was inhibited by LY294002 (5 μmmol/L). Each group was determined for cell proliferation, apoptosis and invasion capabilities, as well as PI3K/AKT transcription and protein expression levels. CITED1 mRNA and protein levels in the siCITED1 group and the siCITED1+LY294002 group were significantly lower than those in the control group (P < 0.05), and the two levels were not significantly different between the LY294002 group and the control group (P > 0.05). Compared with the control group, the siCITED1 group showed remarkably lower proliferation and invasion capabilities, and remarkably higher apoptosis rate (P < 0.05). There was no significant difference in proliferation, apoptosis and invasion capabilities between the LY294002 group and the siCITED1+LY294002 group (P > 0.05), both of which had significantly lower proliferation and invasion capabilities but significantly higher apoptosis rate than the siCITED1 group (P < 0.05). PI3K and AKT protein levels in the siCITED1 group were significantly lower than those in the control group (P < 0.05). The PI3K and AKT protein levels in the LY294002 group and the siCITED1+LY294002 group were not significantly different (P > 0.05), and were significantly lower than those in the siCITED1 group (P < 0.05). In conclusion: CITED1 silence may inhibit the progression of PTC cells by inhibiting the PI3K/AKT pathway.